Synthesis and electrochemical performance of Li2Co1−xMxPO4F (M = Fe, Mn) cathode materials - Khasanova, Nellie R.; Drozhzhin, Oleg A.; Fedotov, Stanislav S.; Storozhilova, Darya A.; Panin, Rodion V.; Antipov, Evgeny V. (Beilstein Journal of Nanotechnology, 2013)
In the search for high-energy materials, novel 3D-fluorophosphates, Li2Co1−xFexPO4F and Li2Co1−xMnxPO4F, have been synthesized. X-ray diffraction and scanning electron microscopy have been applied to analyze the structural and morphological features of the prepared materials. Both systems, Li2Co1−xFexPO4F and Li2Co1−xMnxPO4F, exhibited narrow ranges of solid solutions: x ≤ 0.3 and x ≤ 0.1, respectively. The Li2Co0.9Mn0.1PO4F material demonstrated a reversible electrochemical performance with an initial discharge capacity of 75 mA·h·g−1 (current rate of C/5) upon cycling between 2.5 and 5.5 V in 1 M LiBF4/TMS electrolyte. Galvanostatic measurements along with cyclic voltammetry supported a single-phase de/intercalation mechanism in the Li2Co0.9Mn0.1PO4F material.
Keywords: energy related; fluorophosphates; high-energy cathode materials; high-voltage electrolyte; Li-ion batteries; nanomaterials; reversible capacity